ANALISIS USAHATANI GAMBIR DI DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Apri Helmi; Hainim Kadir; Toti Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted at Tanjung village sub-district of Koto Kampar Hulu the district of Kampar on 2015. The objective of research was to find out how Gambier farming trade done by the society of Gambier farmers at Tanjung village sub-district of Koto Kampar Hulu, The research used premier data obtained directly on the object of research, collected from gambier farmers at Tanjung village sub-district of Koto Kampar Hulu. the population of research was 30 persons of gambier farmers, secondary data was collected from some institutions such as BPS Riau, the data taken was width data and sector production of PDRB farming, citizen data. The data from department of plantation of Kampar was the price of Gambier, industry department and trading was taken from gambir export at Tanjung village sub-district of Koto Kampar Hulu on numeral and monograph data at Tanjung village, and the references were the books from library related to research. Based on the results of research that the success of farmers of gambier at Tanjung village sub-district of Koto Kampar Hulu and influenced by characteristic of social of gambier farmers (farmers identity, adoption process and transformation process of rubber trade to gambier trade) and the characteristic of economy of farmers (capital source, price, marketing, costs, farmer management and farmers income), their marketing was in villages with varieties method, some of farmers sell the gambier to the shop of gambier and through mediators, the obstacles the farmers faced was the decreasing of price and the instruments was broken it inhabitant all activities in gambier processing.Keywords: farm gambier, gambier production factors, characteristics of farming gambier